Comparative evaluation of two nonconventional distillation technologies for separation of ethanol water mixtures by extractive distillation (2018)
In this document, extractive distillation for the separation of Ethanol-Water-ethylene glycol is studied from the conceptual point of view. A methodology for the design of conventional extractive sequences is detailed based on non-linear analysis and the state of the art of extractive distillation. The used methodology can be systematically applied to the design of alternative homogeneous minimum boiling point azeotrope systems. A graphical analysis of extractive distillation sequences is presented by means of the solution of the pinch equations. Obtained pinch branches and column profile maps are analyzed to develop a conceptual based design of an Extractive Dividing Wall Column. This analysis led to reduce the computational effort of designs based on simulation. In order to improve the efficiency of the separation, the obtained designs are studied as a partially diabatic column or a column with Sequential Heat Exchangers (SHE). Finally, an approximation to the application of the results in a pilot scale is made.